2004
DOI: 10.2176/nmc.44.584
|View full text |Cite
|
Sign up to set email alerts
|

Acute Epidural Hematoma Caused by Contrecoup Head Injury-Case Report-

Abstract: A 50-year-old woman presented with a rare case of contrecoup epidural hematoma (EDH) associated with coup EDH. She was hit by a car while riding a bicycle, and struck the left parietal region of her head on the ground. She was dazed for a few minutes. On admission, she complained of nausea but exhibited no neurological deficits. Skull radiography revealed a linear fracture of the left temporal bone. Computed tomography (CT) demonstrated acute EDH in the right frontal region due to contrecoup injury, and thin E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 2 publications
0
25
0
Order By: Relevance
“…Only two other cases satisfied these criteria and they are summarized in the Table with our case for comparison, 12,13 with two further cases involving isolated contrecoup posterior fossa epidural hematoma after forehead impact. 14,15 Conversely, there are several other cases in association with association with coup epidural hematoma 16,17 , subdural hematoma 18 , or contusion 19,20 . In the two previously reported cases, no clear mechanism was found to underlie the development of these lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Only two other cases satisfied these criteria and they are summarized in the Table with our case for comparison, 12,13 with two further cases involving isolated contrecoup posterior fossa epidural hematoma after forehead impact. 14,15 Conversely, there are several other cases in association with association with coup epidural hematoma 16,17 , subdural hematoma 18 , or contusion 19,20 . In the two previously reported cases, no clear mechanism was found to underlie the development of these lesions.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29][30][31] Nakamura reported that the negative pressure in the forehead caused by head injury in the occipital region was 1.6 times the occipital positive pressure, and that the dura of the frontal lobe was susceptible to dissection. 42 The dura mater of the lateral frontal lesion is easily detached from the inner table.…”
Section: Discussionmentioning
confidence: 99%
“…42 The dura mater of the lateral frontal lesion is easily detached from the inner table. [26][27][28][29][30][31] These anatomical mechanisms, together with coagulopathy, may have caused the contrecoup epidural hematoma in the present case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interesting features of patients with contrecoup EDH included: Female predominance, relatively old mean age, high frequency of frontal region involvement, and high rates of delayed appearance of EDH. [9] Delayed EDH is considered uncommon, with a reported incidence of approximately 3%. The peak incidence of EDH is in the second decade, with a mean age of 20-30 years; EDH is rare in patients older than 50-60 years.…”
Section: Sirmentioning
confidence: 99%